Molecular Arrangement and Surface Tension of Alcohol Solutions. - Phan, Chi; Nguyen, C.; Pham, T. (American Chemical Society, 2016)
This study investigated the relationship between molecular arrangement and surface tension of water mixtures with methanol and ethanol. It has been found that the molecular structure of interfacial zone was deterministically correlated to alcohol concentration. From the water dipole moment, an interfacial boundary was defined. The boundary then was used to calculate the water and alcohols in the interfacial zone, which was then used to calculate the surface tension. The prediction from simulated data closely followed the experimental data. The analysis revives the relevance of the molecular arrangement, which had been the main focus in the early 20th century, in quantification of surface energy. The results can supplement the current thermodynamic analysis to correctly predict the surface adsorption.